As Condições de produção das fake news em interface ao discurso do medo - Lage, Lara Rafael (2025)
This study aims to characterize and discuss the interdiscursive relationship between fake news and the discourse of fear as a linguistic-discursive strategy for manipulating information. Lying and deception have always existed, being used as a political tool even before the emergence of the media. However, this phenomenon has intensified with the advent of the internet and social media, which allow for the rapid and massive spread of information that blends truth and falsehood. Although the term translates as "fake news," fake news is not limited to what is true or false, nor even to what is news. Rather, it involves discourses presented in a convincing and sophisticated manner to manipulate, convince, and change the opinions of individuals. Furthermore, fake news is linked to the post-truth era (Bucci, 2019), a scenario in which emotions and personal beliefs have more impact than objective facts, reinforcing narratives guided by individual convictions regardless of their veracity. Therefore, our research interest arises from the concern about the meaning effects that these fraudulent discourses can provoke. Disinformation compromises public debate, weakens democracy, disrupts the information sphere, and directly interferes with public policymaking. Therefore, we mobilized Discourse Analysis, with an emphasis on the contributions of Maingueneau (2007; 2013), whose reflections offer theoretical support for this work. The articulation with Bucci's (2019) assumptions allows us to situate fake news within the current post-truth scenario. The research also draws on studies of the Conditions of Discourse Production, based on the formulations of Courtine (2016) and Orlandi (2001), which allow us to understand how fake news functions within the sociohistorical context of statements. This approach led us to identify an interdiscursivity with the discourse of fear, as discussed by Bauman (2008) and Freud (2010), as this discourse acts as a central element in the construction of persuasion and the emotional mobilization of subjects. To constitute the corpus, the excerpts were organized based on four central themes: human rights, education, health, and security. These were chosen due to their frequency on fact-checking platforms and their relevance in society, as sensitive topics with a high potential for emotional mobilization. We selected two fake news stories from each agency and, from each, two fragments, totaling eight excerpts to develop the analysis for this work. Thus, we used Lupa and Aos Fatos as gateways to fake news. This research revealed that fake news, linked to the discourse of fear, is used as an instrument of political manipulation and strategies of domination and control. These discourses, sustained by personal beliefs and fueled by fear of physical integrity, vulnerability, insecurity, and death, are embedded in the social imaginary with the appearance of truth, influencing perceptions and behaviors. Thus, understanding them through Discourse Analysis allows us not only to unravel their mechanisms of operation but also to reflect on the impacts they have on the constitution of individuals and the social fabric.